Local fauna of bumblebees (Hymenoptera: Apidae: Bombus Latr.) in the outskirts of the town of Kandalaksha, southwest Kola Peninsula - Potapov, GS; Kolosova, YuS; Vlasova, AA (Arctic Environmental Research, 2018)
This article presents the results of research focussed on the local bumblebee fauna in the southwest of the Kola Peninsula (near the town of Kandalaksha). In general, if we include the published data, the local fauna have 16 species of bumblebees. Among the species of the present study, the recent record for this region is Bombus wurflenii Radoszkowski, 1860. This species was previously unknown in the European North of Russia. It is typical for mountain ecosystems in Europe (Scandinavia, the mountains of Central and Western Europe, the Balkans, Northern Turkey and the Caucasus). We assume that the record of B. wurflenii on the Kola Peninsula is the recent appearance of this species in the region. One of the possible reasons for the expansion of this species is climate change. Other species of bumblebees in the local fauna are typical for the region. The species present wide ranges, i.e., Transpalaearctic, Holarctic and one species of West-Central Palaearctic. In the outskirts of Kandalaksha, there are 2 species (B. distinguendus Morawitz, 1869 and B. veteranus (Fabricius, 1793)) which belong to the group of meadow species according to their habitat preference. They are not common for the taiga habitats in the European North of Russia. We can explain their presence in the local fauna by noting the presence of anthropogenic meadow habitats in the studied area.